INTRAMUSCULAR DICLOFENAC Vs PERIPROSTATIC LIDOCAINE INJECTION FOR CONTROLLING PAIN UNDERGOING TRANSRECTAL ULTRASOUND GUIDED PROSTATIC BIOPSY - Alam, Syed Iftikhar; ullah, Hazrat; Kibria, Zeeshan; Masood, Iqra; Jawed, Rubab (Journal of Ayub Medical College Abbottabad, 2017)
Background: Transrectal ultrasound (TRUS) technique for getting prostatic tissue for histopathology is now the standard procedure for malignant lesions of the prostate and imperative diagnostic investigation of patients with clinical specks of prostatic neoplasia. During TRUS guided biopsy, pain control has been important issue therefore, highly potent analgesia before this procedure should be considered on high priority according to current census. Therefore, we compared intramuscular diclofenac injection with sensory blockade of injection lidocaine to abolish pain undergoing prostatic biopsy with TRUS technique. Methods: Total 200 patients were selected for this study having raised PSA values and suspicious nodule on Digital Rectal Examination. These patients were segregated into two groups by randomization. Group A received intramuscular diclofenac and group B were infiltrated with lidocaine injection for sensory blockade. Results: Patients in group A was having mean age of 64.5±5.8 years while for group B patients was 65.6±4.9 years (p=0.16). Both groups have statistically insignificant difference in their mean PSA values (p=0.24) and mean prostatic volume (p=0.22). The mean pain scores on visual analogue scale in groups A was 3.5±0.8 and in group B it was 2.4±0.8 (p<0.001). 60% group A patients reported with mild or no pain compared to 90% in group B. (p<0.001). Conclusion: Local blockade with lidocaine injection has better pain control as compared to patients experienced pain with intramuscular diclofenac used for prostatic biopsy through TRUS technique. Keywords: Transrectal Ultrasound; Biopsy; Periprostatic block; Diclofenac; Lidocaine; Prostate